Love, sex and marriage : the circulation of sexual knowledge in Singapore, 1965 to 1985 - Toh, Xun Qiang (2019)
In Singapore, sexual knowledge is contained to the domestic sphere. The establishment of the Singapore Family Planning and Population Board in 1966 institutionalised the dissemination of family planning and contraceptive knowledge, while the ongoing launching the Anti-Yellow Culture Campaign restricted the circulation of sexually explicit publications. Amidst the campaign, sex education was left to function independently, provided in missionary schools and held voluntarily by medical professionals. Family life education however, was also institutionalised in schools, taught under moral education since 1967. A revamp of moral education occurred in 1979, but sex education continues to be neglected in the revised syllabus. By the 1980s, the efforts of medical professionals in providing sex education intensified. This thesis examines how sexual knowledge was constructed and circulated Singapore between 1965 and 1985. Existing literature focuses on the state’s dominant role in shaping sexual knowledge through family policies. This paper endeavours to provide a bigger picture by incorporating the efforts of non-state actors that contributed to the discourses on sexuality as well. I argue that sexuality primarily served to entrench the political legitimacy of the state between 1965 and 1985.